From the Inside (Res Medica, 2014)
LetterWe are often told, "You don't know what it feels like." This is often true, to imagine the plight felt by someone facing the consequences of a terminal illness will more than stretch empathy. Edinburgh medics face a newer, more intense form of this human misery, a cohort of young, vital people, cornered by drug addiction and threatened by AIDS. We present here a moving letter sent to RES MEDICA by a local drug user with HIV.